Research of the Regional Service Market in Terms of International Economic Activity’s Customs Registration - Fedorenko, Roman V.; Persteneva, Natalia P.; Konovalova, M. E.; Tokarev, Y. A. (International Journal of Economics and Financial Issues, 2016)
The article states the economic essence of Ñustoms registration, its significance for the development of international economic activity in the present context. The customs’ service development problem relevance is stipulated by the necessity to develop any state’s international economic activity. Key trends of the service market development in the customs sphere have been revealed, the perspectives of subjective development of complex services in the customs sphere have been defined in terms of the carried out retrospective as well as the structural and functional analysis. The regional service market in terms of customs registration, its dynamics and structure, its interrelations and interdependencies have been examined using economic and mathematical methods. Keywords: International economic activity; Customs service; Customs representative; Services in the customs sphere. JEL Classifications: C01; F18; L19